Why is spirometry underused in the diagnosis of the breathless patient: a qualitative study - Partridge Martyn R; Smith Susan F; Roberts Nicola J (BMC Pulmonary Medicine, 2011)
Abstract Background Use of spirometry is essential for the accurate diagnosis of respiratory disease but it is underused in both primary and specialist care. In the current study, we have explored the reasons for this underuse. Methods Five separate focus groups were undertaken with final year medical undergraduates, junior hospital doctors, general practitioners (GPs) and specialist trainees in respiratory medicine. The participants were not told prior to the session that we were specifically interested in their views about spirometry but discussion was moderated to elicit their approaches to the diagnosis of a breathless patient, their use of investigations and their learning preferences. Results Undergraduates and junior doctors rarely had a systematic approach towards the breathless patient and tended, unless prompted, to focus on the emergency room situation rather than on patients with longer term causes of breathlessness. Whilst their theoretical knowledge embraced the possibility of a non-respiratory cause for breathlessness, neither undergraduates nor junior doctors spontaneously mentioned the use of spirometry in the diagnosis of respiratory disease. When prompted they cited lack of familiarity with the use and location of equipment, and lack of encouragement to use it as being major barriers to utilization. In contrast, GPs and specialist respiratory trainees were enthusiastic about its use and perceived spirometry as a core element of the diagnostic workup. Conclusions More explicit training is needed regarding the role of spirometry in the diagnosis and management of those with lung disease and this necessitates both practical experience and training in interpretation of the data. However, formal teaching is likely to be undermined in practice, if the concept is not strongly promoted by the senior staff who act as role models and trainers.